2013
DOI: 10.1371/journal.pone.0070423
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic Status of Laparoscopic Urologic Surgery: Survey Results from 241 Urologic Surgeons in China

Abstract: BackgroundThe prolonged and frequent use of laparoscopic equipment raises ergonomic risks that may cause physical distress for surgeons. We aimed to assess the prevalence of urologic surgeons’ physical distress associated with ergonomic problems in the operating room (OR) and their awareness of the ergonomic guidelines in China.MethodsA sample of 300 laparoscopic urologists in China was assessed using a questionnaire on demographic information, ergonomic issues in the OR, musculoskeletal symptoms, and awarenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 27 publications
2
28
0
1
Order By: Relevance
“…The majority (83.3%) comprised cross-sectional studies. Within this type of methodology, the main issues addressed in the studies on physical health were musculoskeletal disorders (AUeRBACH et al, 2011;MeHRDAD;DeNNeRLeiN;MORDHeSiZADeH, 2012;RUiTeNBURG;FRiNGS-DReSeN;SLUiTeR, 2013;MOHSeNi-BANDPei et al, 2011;LiANG et al, 2013) and ophthalmologic health (MReNA et al, 2011;KRUPiNSKi;BeRBAUM, 2009 Rauchenzauner et al (2009) found that frequent stressing situations, sleep deficit, and deregulation of the circadian rhythm are causes of the incidence of cardiovascular diseases in this group of professionals. Before the manifestation of symptoms of cardiovascular diseases, after night shifts physicians presented an increase in the cardiac frequency, as well as the elevation of blood pressure, dysrhythmia, altered catecholamine secretion, and an increase of serum cholesterol, uric acid, and potassium.…”
Section: Physical Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority (83.3%) comprised cross-sectional studies. Within this type of methodology, the main issues addressed in the studies on physical health were musculoskeletal disorders (AUeRBACH et al, 2011;MeHRDAD;DeNNeRLeiN;MORDHeSiZADeH, 2012;RUiTeNBURG;FRiNGS-DReSeN;SLUiTeR, 2013;MOHSeNi-BANDPei et al, 2011;LiANG et al, 2013) and ophthalmologic health (MReNA et al, 2011;KRUPiNSKi;BeRBAUM, 2009 Rauchenzauner et al (2009) found that frequent stressing situations, sleep deficit, and deregulation of the circadian rhythm are causes of the incidence of cardiovascular diseases in this group of professionals. Before the manifestation of symptoms of cardiovascular diseases, after night shifts physicians presented an increase in the cardiac frequency, as well as the elevation of blood pressure, dysrhythmia, altered catecholamine secretion, and an increase of serum cholesterol, uric acid, and potassium.…”
Section: Physical Healthmentioning
confidence: 99%
“…The most common ergonomic risks reported were spending long periods standing, sitting, and neck in flexion. Liang et al (2013) found that the increase on the incidence of numbness, pain and stiffness in the neck, shoulders, back, and legs of urologist surgeons was related to the emergence of surgical techniques that are less invasive but ergonomically less favorable.…”
Section: Physical Healthmentioning
confidence: 99%
“…Based on some studies, more than half of the surgeons prefer to use manual control instead of the pedal because of its discomfort and consequences. Monitor's position is another major ergonomic factor leading to improper use of the pedal (1,25). Unfortunately, as some operating rooms in this study had only one monitor, first assistants and operating room nurses had to turn the monitor to have a good view.…”
Section: Discussionmentioning
confidence: 93%
“…Questionnaires are another assessment tool that focuses on gathering information from a population of surgeons. Taking into account studies with at least 100 respondents, a survey to laparoscopic urologists in China concluded that most of them were not aware of the ergonomic guidelines for the OR [36]. Shoulder, neck, back, and hand pain and stiffness were reported as the main physical symptoms during laparoscopic procedures [36,37].…”
Section: Questionnairesmentioning
confidence: 99%